2021
DOI: 10.1038/s41598-021-82072-z
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin is a marker of cardiovascular mortality in patients with chronic kidney disease stages 3–5

Abstract: Cardiovascular disease (CVD) is the leading cause of death in patients with chronic kidney disease (CKD). Osteoprotegerin (OPG), known to regulate bone mass by inhibiting osteoclast differentiation and activation, might also play a role in vascular calcification. Increased circulating OPG levels in patients with CKD are associated with aortic calcification and increased mortality. We assessed the predictive role of OPG for all-cause and cardiovascular mortality in patients with CKD stages 3–5 over a 5-year fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…Another bone-protective factor, OPG, prevents mineral resorption by inhibiting osteoclast differentiation and activation, but it is associated with greater cardiovascular disease. Consistent with other reports, a study of over 100 patients with CKD showed significantly greater all-cause and cardiovascular mortality in those with higher baseline OPG levels [160]. Since monocyte/macrophages and osteoclasts share common myeloid precursors, attempts have been made to activate RANK signaling in myeloid cells in vivo.…”
Section: Outlook On Therapeutic Targetssupporting
confidence: 77%
“…Another bone-protective factor, OPG, prevents mineral resorption by inhibiting osteoclast differentiation and activation, but it is associated with greater cardiovascular disease. Consistent with other reports, a study of over 100 patients with CKD showed significantly greater all-cause and cardiovascular mortality in those with higher baseline OPG levels [160]. Since monocyte/macrophages and osteoclasts share common myeloid precursors, attempts have been made to activate RANK signaling in myeloid cells in vivo.…”
Section: Outlook On Therapeutic Targetssupporting
confidence: 77%
“…35 Accordingly, elevated serum OPG levels were associated with higher all-cause and cardiovascular 5-year mortality risk, independent of age, CVD, diabetes, and inflammatory markers, in patients with CKD stages 3-5. 36 Most of these studies were performed in diabetic patients, and suggest OPG to be a biomarker of CKD progression. 37,38 Our findings were confirmed on mixed population of diabetic and non-diabetic subjects at different CKD stages, therefore bring novel arguments as to the use of OPG as a mortality predicting marker in CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the debate on the role of circulating OPG in atherosclerotic disease [ 31 ], as an experimental study reported that exogenous OPG treatment lead to endothelial and vascular smooth cell dysfunction by promoting the production of reactive oxygen species, which may underlie vascular injurious effects in conditions such as hypertension [ 32 ], the phenotype of OPG-knockout mice ultimately indicates circulating OPG as a biomarker, rather than a mediator, of atherosclerosis, as OPG-deficient mice develop early onset arterial calcification [ 33 ]. In this context, the association of high serum OPG level with coronary artery calcification [ 15 , 16 ], and cardiovascular [ 17 , 18 ] and all-cause mortality [ 19 , 20 ] in patients with CKD has been suggested. The association between serum OPG level with long-term visit-to-visit BPV presented in this study highlights a novel role of circulating OPG as a biomarker that predict a surrogate of CV events.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that high serum OPG level is associated with the presence [ 15 ] and severity [ 16 ] of coronary artery calcification in patients with CKD. In this regard, elevated circulating OPG level has been proposed as a predictor of cardiovascular [ 17 , 18 ] and all-cause [ 19 , 20 ] mortality in patients with CKD. Serum OPG level is positively associated with peripheral artery disease, arterial stiffness, and arterial calcification in patients with end-stage renal disease [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%